Pre-service Teachers’ Perceptions on the Relationship between Learning Program Design Course and Their Teaching Preparations - Elizabeth Liza; Ouda Teda Ena (Premise: Journal of English Education and Applied Linguistics, 2019)
Learning Program Design is one of the compulsory courses offered to the English Language Education Study Program (ELESP) students to prepare for their teaching. This study is aimed to find out and to identify the possible relationship between Learning Program Design course and students’ teaching preparations. A survey study was conducted. The instrument used was questionnaire. A total of 30 students participated in this study. The perceptions of the pre-service teachers were obtained from their self-evaluations. The results of this study showed that most of the respondents had positive attitudes. They perceived that Learning Program Design Course had positive contributions to their teaching preparations.